If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + 15x = -1x + -3 Reorder the terms: 29 + 15x = -3 + -1x Solving 29 + 15x = -3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 29 + 15x + x = -3 + -1x + x Combine like terms: 15x + x = 16x 29 + 16x = -3 + -1x + x Combine like terms: -1x + x = 0 29 + 16x = -3 + 0 29 + 16x = -3 Add '-29' to each side of the equation. 29 + -29 + 16x = -3 + -29 Combine like terms: 29 + -29 = 0 0 + 16x = -3 + -29 16x = -3 + -29 Combine like terms: -3 + -29 = -32 16x = -32 Divide each side by '16'. x = -2 Simplifying x = -2
| 65=5-8x+2x | | 3x-8=4y+4 | | x-0.10=63 | | (2/3)n+8=0.5n+2 | | 2g+12=28 | | x^2-7x-294=0 | | -8(5t-4)+t=32 | | 4-6x=7-3x | | 14-3t+t-5=-4-1 | | -2(3y-6)+4(5y-8)=-18 | | 8-2x=24-8x | | 19x-7=7+12x | | 14-3t+t-5=-4-2 | | 2x+4=3y | | 4x-15=1+x | | 12x-40=24-8x | | 3y=2x+4 | | 5x-4(0)=60 | | x-8+8=-x | | 4x+3=7x-4x | | -4-5x=-21-3x | | 2.3w-11=-1.75w | | 2x^2-4y=24 | | 5(0)-4y=60 | | b-9+3b=24 | | 8p+12q= | | 2r-3+3=-r | | 5-4(2x-3)=13 | | 3x-23=7x+17 | | 8p-3(p-6)=-7 | | 4t+1=t+5+t-3 | | 3-6=9 |